Monsoon Rainfall Prediction in TamilNadu Using Data Mining Techniques - S.Sakthivel, Dr.(Mrs.) G.Thailambal (International Journal of Advanced Science and Technology, 2020)
Tamilnadu is one of the agricultural state in India, the state maintain essential food production based on rainfall and the water reservoirs. Water reservoirs also get huge amount of water from rain the state get more rain from monsoon rainfall. The state has two type of monsoons in the year first one is North-East Monsoon (NEM), the next one is South-west monsoon (SWM) in Tamilnadu get more than fifty percentage of rain from North-East monsoon rainfall. So this paper mainly analysing monsoon rainfall. The precipitation expectation has been one of the most challenging problems in today’s modern science and technology because now a days the various factors affect accurate predictions such as climate changing, global warming and destroying forests, this paper analysing these challenges and give possible solutions.